1976
DOI: 10.1111/j.1365-2230.1976.tb01398.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coal tar fractions on guinea-pig and human skin

Abstract: Summary In this study, the effect of topical applications of coal tar and of fractions derived from it were investigated in guinea‐pigs and humans. Coal tar and its fractions produced thickening of guinea‐pig epidermis in various degrees which were accurately measured. There was great variability in the epidermal thickening caused by different batches of coal tar. Separation into ether soluble and insoluble fractions yielded products which caused greater epidermal thickening than the parent substance. The acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Furthermore, their observations on the pharmacological variability of coal tar are not new. This was first demonstrated by Downing & Bauer (1948) and confirmed in later studies (Wrench & Britten, 1975;Sarkany & Gaylarde, 1976). In addition we reported data on the effect of various coal tar fractions on epidermal thickness and showed that coal tar and certain of its fractions could suppress epidermal thickening induced by a topically applied irritant.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, their observations on the pharmacological variability of coal tar are not new. This was first demonstrated by Downing & Bauer (1948) and confirmed in later studies (Wrench & Britten, 1975;Sarkany & Gaylarde, 1976). In addition we reported data on the effect of various coal tar fractions on epidermal thickness and showed that coal tar and certain of its fractions could suppress epidermal thickening induced by a topically applied irritant.…”
supporting
confidence: 81%
“…They cited previous publications which supported their work. They ignored the majority of reports which disagreed with their findings and which reported an increase in mitotic rate labelling index or epidermal thickness (Jambon, 1909;Combes, 1943;Kaidbey & Kligman, 1974;Elgjo & Larsen, 1973;Saldfeld & Orth, 1965;Wrench & Britten, 1975;Foreman et al, 1979;Sarkany & Gaylarde, 1976).…”
mentioning
confidence: 96%
“…Furthermore, Jambon (1909) observed an increased mitotic rate when tar was applied to normal human skin. Epidermal hyperplasia has also been found in hairless mice (Elgjo & Larscn, 1973) and guinea-pigs (Sarkany & Gaylarde, 1976). However, in all of these studies the duration was short (4 weeks or less).…”
Section: Discussionmentioning
confidence: 93%
“…In a recent study in whleh the effects of coal tar and vitamin A acid on membrane coating granules were analyzed (Lavker, Grove & Leyden, 1979), we gained the impression that the epidermis was thinner after the tar treatment. This was a paradoxical result for coal tar is known to produce hyperplasia and hyperkeratosis in man (Jambon, 1909;Combes, 1943Combes, ,1944Kaidbey& Kligman, 1974) and animals (Sarkany & Gaylarde, 1976;Elgjo & Larscn, 1973).…”
mentioning
confidence: 99%
“…The action of the dithranol vehicle on the epidermis measured in this study is probably due to the presence of coal tar. Coal tar stimulates epidermal turnover in normal skin but causes suppression of epidermal hyperplasia in psoriasis [27] and of thickening induced by irritants [28]. A suppression of epidermal DNA synthesis has been suggested [29].…”
Section: Discussionmentioning
confidence: 99%